Experimental investigation of gas–oil–water phase flow in vertical pipes: influence of gas injection on the total pressure gradient - Ganat, Tarek A.; Hrairi, Meftah; Regassa, Shiferaw (Springer Link, 2019)
Experimental work has been conducted to study the infuence of gas injection on the phase inversion between oil and water fowing in a vertical pipe. A vertical transparent pipe test section line of 40 mm ID and 50 cm length was used. The test fuids used were synthetic oil and fltered tap water. Measurements were taken for mixture velocity, superfcial water velocity, superfcial gas velocity, and input superfcial oil velocity ranging from 0.4 to 3 m/s, 0.18 to 2 m/s, 0 to 0.9 m/s, and 0 to 1.1 m/s. Most of the experiments were conducted more than two times, and the reproducibility of the experiments was quite good. Special attention was given to the efect of oil and water concentration where phase inversion took place with and without gas injection. The results showed that the phase inversion point was close to water fraction of ~30%, for both water friction direction changes (from water to oil or from oil to water) and that the efective viscosity increases once the mixture velocity increases. On the other hand, the results with gas injection showed that gas injection had no efect on the oil or water concentration where phase inversion occurred. Furthermore, the study investigated the efect of gas–oil–water superfcial velocity on the total pressure gradient in the vertical pipe. It was found that the total pressure gradient was fast and increased at high superfcial gas velocity but was slow at low superfcial gas velocity. When the superfcial oil velocity increased, the total pressure gradient approached the pressure gradient of an oil–water two-phase fow. The obtained results were compared with few correlations found in the literature, and the comparison showed that the uncertainty of the fow pattern transition peak in this study is very low